Conductive gel based on lithium iron phosphate waste and preparation method thereof
By using lithium iron phosphate waste and a composite solvent system to prepare conductive gels, the problems of high cost and complex recycling processes of traditional conductive gels are solved, enabling low-cost, high-performance conductive gel applications suitable for electrocatalysis and flexible electronic devices.
Patent Information
- Application Number
- CN202511334487.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-18
- Publication Date
- 2025-11-21
AI Technical Summary
Traditional conductive gels are costly and have complex processes. Metal fillers are prone to oxidation and deactivation, and carbon-based materials have poor dispersibility, making it difficult to achieve large-scale application. Furthermore, traditional methods for recycling lithium iron phosphate waste are complex, energy-intensive, and prone to secondary pollution, making it difficult to achieve high-value utilization.
Pretreated lithium iron phosphate waste was used as a conductive filler, dispersed in an NMP/methanol or water/ethanol composite solvent system, and mixed with polyvinylpyrrolidone (PVP). Conductive gel was prepared by ultrasonic dispersion and a simple gelation process, which simplifies the process and reduces costs.
This invention achieves a low-cost, high-conductivity conductive gel, significantly reducing preparation costs and energy consumption, improving filler dispersibility and interfacial bonding strength, and forming a stable conductive network, suitable for electrocatalysis and flexible electronic devices.
Smart Images

Figure CN120988313A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the field of functional materials and resource recycling technology, and particularly relates to a conductive gel based on lithium iron phosphate waste and a preparation method thereof. BACKGROUND
[0002] As a functional material with both conductivity and deformability, the conductive gel has wide application in the fields of flexible electronics, energy storage and sensors. The conductive gel realizes charge transmission by embedding conductive fillers into a gel matrix, and is commonly used in electrode interfaces, wearable devices and flexible sensors. Traditional conductive gels usually use metal nanoparticles such as silver nanowires or carbon-based materials such as graphene and carbon nanotubes as fillers. Although the conductivity is good, the cost is high and the process is complex. Metal fillers are easily oxidized and inactivated, and carbon-based materials have poor dispersibility, which seriously restricts their large-scale application. Therefore, developing a low-cost, high-performance and simplified process conductive gel has become the key to promoting the development of flexible electronics technology.
[0003] As a mainstream positive electrode material of lithium ion batteries, lithium iron phosphate (LiFePO4) still has significant resource potential after being retired. The material itself has ion / electron conductivity, chemical stability and layered structure, and can be converted into functional conductive fillers after pretreatment. The traditional recycling method mainly focuses on extracting valuable metals (such as lithium, iron and phosphorus) by fire or wet method, which has the problems of complex process, high energy consumption and easy secondary pollution, and is difficult to realize high-value utilization. If the pretreated lithium iron phosphate waste is directly used to construct conductive gel, it can greatly reduce the cost of raw materials, and also help to realize the resource recycling of solid waste, which has economic and environmental benefits.
[0004] The selection of gel matrix and solvent system is the core of constructing high-performance conductive gel. Common polymer matrices such as PVP, PVA and PVDF have good film-forming property and chemical stability, but their processing often depends on strong polar solvents such as N-methyl pyrrolidone (NMP). The single NMP system has high cost and heavy environmental burden, while the introduction of co-solvents such as methanol, water or ethanol can effectively adjust the solution viscosity, improve the filler dispersibility and reduce the preparation cost. By optimizing the proportion of composite solvents and the gelation process (such as solvent evaporation induced molding or low temperature crosslinking), uniform dispersion and stable combination of fillers in the gel network can be realized, forming efficient conductive paths.
[0005] The present application uses pretreated lithium iron phosphate waste as a conductive filler, disperses it in an NMP / methanol (or water / ethanol) composite solvent system, and composites it with a gel matrix. Through a homogenization and simple gelation process, a low-cost, high-conductivity composite gel material is successfully prepared. The material makes full use of the inherent conductive properties of lithium iron phosphate, the designability of the gel matrix, and the processing adaptability of the composite solvent, and exhibits excellent conductive stability, flexibility, and interface bonding strength, providing a high-performance and sustainable material solution for the fields of electrocatalysis and flexible electronic devices. SUMMARY
[0006] In view of this, the present application proposes a conductive gel based on lithium iron phosphate waste and a preparation method thereof to solve the problems in the technical background. The low-cost conductive gel can replace traditional nafion, acetylene black conductive gel (also known as ink), and metal conductive gel, improve the conductivity of materials under various conditions, and solve the problems of complex process, high energy consumption, and secondary pollution in traditional recycling processes, and the difficulty in realizing high-value utilization of waste materials. The present application uses lithium iron phosphate waste instead of metal nanoparticles and carbon-based materials to prepare a point gel, significantly simplifying the preparation process and cost of the conductive gel, and providing a low-cost and simple solution for applications that require conductivity and processability, such as electrocatalytic gel, flexible electronics, sensors, and electrode interfaces. Specifically, the present application includes the following contents:
[0007] A conductive gel based on lithium iron phosphate waste uses lithium iron phosphate waste powder as a conductive filler and a composite gel prepared by mixing polyvinylpyrrolidone (PVP) and methanol solution and N-methylpyrrolidone (NMP) as a matrix. The composite gel is prepared by ultrasonic dispersion. The lithium iron phosphate waste powder is a fine powder crushed and passed through a 200-mesh sieve. The conductivity of the conductive gel is better than that of a conductive gel using acetylene black as a conductive filler.
[0008] Further, the lithium iron phosphate waste is collected and ground into a powder state without lumping. The conductivity of the conductive gel is tested by attaching it to a carbon cloth.
[0009] A preparation method of a conductive gel based on lithium iron phosphate waste, which specifically includes the following steps:
[0010] Step 1, preparation of a composite gel: weigh PVP and add it to a 99% mass fraction methanol solution, stir at room temperature to obtain a uniform mixed solution, then slowly stir and dissolve in the NMP mixed solution, and then seal and store the prepared composite gel in a refrigerator;
[0011] Step 2, pretreatment of lithium iron phosphate powder: the lithium iron phosphate waste powder is crushed in a mortar, then sieved with a 100 mesh sieve for the first time, the fine powder is again put into the mortar for secondary grinding and sieving, and the second sieving is performed with a 200 mesh sieve. The ground lithium iron phosphate powder is ready for use.
[0012] Step 3, preparation of lithium iron phosphate conductive gel: the ground powder is uniformly ultrasonicated with the composite gel to obtain a black lithium iron phosphate waste conductive gel.
[0013] Step 4, test the conductivity of the lithium iron phosphate conductive gel: 60 microliters of the conductive gel is uniformly coated on the carbon cloth, and placed in a blast oven for overnight drying at a temperature of 60°C.
[0014] Further, in step 3, ultrasonic to the surface layer of ash-free black powder.
[0015] Further, in step 1, the heat stirring is performed for 24h, if the gel is not transparent, but still milky white, the stirring should be continued until the gel is transparent, which ensures the complete dissolution of PVP.
[0016] Further, in step 1, 20mg of ground lithium iron phosphate powder is weighed for use, 20mg of PVP is added to a centrifuge tube, 4mL of methanol is added, and the mixture is stirred at room temperature to obtain a uniform solution. 2mL of NMP is slowly added and stirred, and the mixture is stirred at 40°C for 24h to completely dissolve.
[0017] Further, the weighed lithium iron phosphate waste powder is added to the obtained transparent composite gel, and ultrasonic is performed for 60min at a power of 300W to completely dissolve the lithium iron phosphate waste powder, and a black lithium iron phosphate waste conductive gel is obtained.
[0018] Further, the methanol can be replaced by water or ethanol.
[0019] The above technical solution has the following beneficial effects:
[0020] The application embeds the pretreated lithium iron phosphate waste as a conductive filler into a gel matrix, uses an N-methyl pyrrolidone / methanol (or water, ethanol) composite solvent system to realize uniform dispersion and controllable gelation, realizes the synergistic effect of "waste value-added-performance improvement", and the intrinsic ion / electron conduction channel of the lithium iron phosphate waste retains the efficient charge transport network of the gel, the rigid particle structure enhances the mechanical strength of the gel, and the composite solvent system optimizes the rheological property to ensure uniform dispersion of the filler, forming a stable conductive-mechanical double network. Among them, NMP and PVP ensure that the gel matrix is fully dissolved and combined at the interface, the methanol / water / ethanol cosolvent reduces the viscosity of the system, improves the wettability of the filler, reduces the amount of expensive solvent by more than 30%, and the introduction of water or ethanol also reduces the dependence on toxic solvents, in line with the trend of green manufacturing. In terms of process, through solvent volatilization induced forming or low temperature crosslinking process (<100℃), high temperature energy consumption is avoided, the conductive structure of the waste filler and the integrity of the gel network are completely retained, the energy consumption is reduced by about 60% compared with the traditional process, and the preparation cost is reduced by about 70%. In terms of performance, the chemical inertness of the waste filler and the encapsulation effect of the gel make its conductivity maintain good performance in the Na2SO4 environment test, and the waste / gel interface is tightly bonded by solvent induction and resistant to organic solvent erosion. Compared with traditional metal / carbon-based conductive gels, the composite gel material of the application has lower raw material cost, better environmental adaptability and simpler manufacturing process, providing a good solution for sustainable development and providing high-performance conductive gels. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 SEM images of lithium iron phosphate powder pretreated for Examples 1 and 2;
[0022] Figure 2 LSV performance graph for Example 1;
[0023] Figure 3 SEM images of the conductive gel prepared in Example 1 attached to carbon cloth.
[0024] Figure 4 SEM images of the conductive gel prepared in Example 1 attached to carbon cloth and after use.
[0025] Figure 5 LSV performance graph of Example 2 doped with rare earth metal salt;
[0026] Figure 6 Graph of mil-100(Fe) prepared using lithium iron phosphate gel having high cycle stability;
[0027] Figure 7 Graph of Example of OCP lithium iron phosphate gel having better ion transport efficiency than the base NMP gel. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the protection scope of the present application.
[0029] Embodiment 1, see Figures 1-4 A lithium iron phosphate waste-based conductive gel for attaching to carbon cloth for improving electrocatalytic OER performance and a material preparation method thereof are shown in the following steps:
[0030] Step 1, lithium iron phosphate waste pretreatment: 100 g of lithium iron phosphate waste is weighed and added to a medicine powder machine for grinding for 30 s, then poured into a 100-mesh filter screen for screening, and repeated 2-5 times to complete the first screening. The screened lithium iron phosphate waste is poured into the medicine powder machine again, and the above steps are repeated, but a 200-mesh filter screen is used for the second screening.
[0031] Step 2, preparation of lithium iron phosphate conductive gel: 20 mg of finely ground lithium iron phosphate powder is weighed for standby, 20 mg of PVP is added to a centrifuge tube, and 4 mL of methanol is added, and a uniform mixed solution is obtained by stirring at room temperature. Then slowly add 2 mL of NMP and stir, stir at 40°C for 24 h to completely dissolve. Add the weighed lithium iron phosphate waste powder to the obtained transparent mixture, and ultrasonicate (power 300 W) for 60 min to completely dissolve, to obtain a black conductive gel (if the demand for conductive gel is large, it can be prepared in proportion).
[0032] Step 3, preparation of electrode material: the carbon cloth is cut to 1×1.7 cm to ensure that 1×1 cm is immersed in the liquid during use. The cut carbon cloth is placed in dilute hydrochloric acid and ultrasonicated for 30 s to remove surface impurities and washed with deionized water for 3 times. 60 microliters of lithium iron phosphate conductive gel is applied to the carbon cloth, and the electrode material is obtained by drying in an oven overnight.
[0033] The LSV of the carbon cloth attached with ordinary gel and lithium iron phosphate conductive gel in this embodiment shows that the electrode material attached with the gel has better conductivity and the oxygen evolution potential is advanced.
[0034] Embodiment 2, see Figure 1 and Figure 5 A lithium iron phosphate waste-based conductive gel for attaching to carbon cloth for improving electrocatalytic degradation of organic matter and a material preparation method thereof are shown in the following steps:
[0035] Step 1, lithium iron phosphate waste pretreatment: take 100g lithium iron phosphate waste and put it into a medicine powder machine for 30s grinding, then pour it into a 100 mesh filter screen for screening, repeat 2-5 times to complete the first screening, and then pour the screened lithium iron phosphate waste into the medicine powder machine again and repeat the above steps, but use a 200 mesh filter screen for the second screening.
[0036] Step 2, preparation of Ce-doped lithium iron phosphate conductive gel: take 20mg of finely ground lithium iron phosphate powder and 20mg of Ce(NO3)3·6H2O, add 20mg of PVP and 4mL of methanol to a centrifuge tube, stir at room temperature to obtain a uniform mixed solution. Then slowly add 2mL of NMP and stir, stir at 40°C for 24h to completely dissolve. Add the weighed lithium iron phosphate waste powder and 20mg of Ce(NO3)3·6H2O to the resulting transparent mixture, and ultrasonic (power 300W) for 60min to completely dissolve, to obtain a black conductive gel.
[0037] Step 3, preparation of Pr-doped lithium iron phosphate conductive gel: take 20mg of finely ground lithium iron phosphate powder and 20mg of Pr(NO3)3·6H2O, add 20mg of PVP and 4mL of methanol to a centrifuge tube, stir at room temperature to obtain a uniform mixed solution. Then slowly add 2mL of NMP and stir, stir at 40°C for 24h to completely dissolve. Add the weighed lithium iron phosphate waste powder and 20mg of Pr(NO3)3·6H2O to the resulting transparent mixture, and ultrasonic (power 300W) for 60min to completely dissolve, to obtain a black conductive gel.
[0038] Step 4, preparation of electrode material: take carbon cloth and cut it to 1×1.7cm to ensure that 1×1cm is immersed in liquid during use, put the carbon cloth into dilute hydrochloric acid and ultrasonic for 30s to remove surface impurities and clean with deionized water for 3 times, take 60 microliters of gel containing rare earth metal doping and apply it to the carbon cloth, put it into an oven and dry overnight to obtain the electrode material.
[0039] The lithium iron phosphate waste-based conductive gel of the present embodiment has excellent conductivity, through LSV analysis, the rare earth metal-doped conductive gel has high conductivity and can delay the release of oxygen under working conditions, can generate a large amount of oxidative free radicals in water and can be applied to the field of electrocatalytic degradation of oxides in harsh environments.
[0040] The above describes the basic principles and main features of the present application, and those skilled in the art should understand that the present application is not limited to the above embodiments, and the above embodiments and descriptions in the specification are only to illustrate the principles of the present application, and various changes and improvements can be made without departing from the spirit and scope of the present application, and these changes and improvements all fall within the scope of the claimed present application, and the scope of protection is defined by the appended claims and their equivalents.
Claims
1. A conductive gel based on lithium iron phosphate waste, characterized in that, The conductive gel is prepared by ultrasonic dispersion using lithium iron phosphate waste powder as conductive filler and a composite gel prepared by mixing polyvinylpyrrolidone (PVP), methanol solution, and N-methylpyrrolidone (NMP) as matrix. The lithium iron phosphate waste powder is fine powder that has been crushed and passed through a 200-mesh sieve. The conductivity of the conductive gel is better than that of the conductive gel using acetylene black as conductive filler.
2. The conductive gel based on lithium iron phosphate waste according to claim 1, characterized in that, The lithium iron phosphate waste is collected and ground into a fine powder without any lumps or agglomeration, and the conductivity of the conductive gel is tested by adhering it to carbon cloth.
3. A method for preparing a conductive gel based on lithium iron phosphate waste, characterized in that, The specific preparation includes the following steps: Step 1, Preparation of composite gel: Weigh PVP and add it to a 99% methanol solution. Stir at room temperature to obtain a homogeneous solution. Then, slowly stir and dissolve it in an NMP solution. Finally, seal and refrigerate the prepared composite gel. Step 2, Pretreatment of lithium iron phosphate powder: The lithium iron phosphate waste is crushed in a powder mill, and then sieved for the first time using a 100-mesh sieve. The fine powder is then poured back into the powder mill for a second grinding and sieved again using a 200-mesh sieve. The finely ground lithium iron phosphate powder is ready for use. Step 3, Preparation of lithium iron phosphate conductive gel: The finely ground powder and composite gel are ultrasonically homogenized to obtain black lithium iron phosphate waste conductive gel. Step 4: Test the conductivity of lithium iron phosphate conductive gel. Take 60 microliters of conductive gel, spread it evenly on carbon cloth, and place it in a forced-air drying oven at 60°C overnight.
4. The method for preparing a conductive gel based on lithium iron phosphate waste according to claim 3, characterized in that, In step 3, ultrasonication is performed until no gray-black powder remains on the surface.
5. The method for preparing a conductive gel based on lithium iron phosphate waste according to claim 3, characterized in that, In step 1, the mixture is kept warm and stirred for 24 hours. If the gel is not transparent and is still milky white, it must be stirred until it becomes transparent before it can be used. This ensures the complete dissolution of PVP.
6. The method for preparing a conductive gel based on lithium iron phosphate waste according to claim 3, characterized in that, In step 1, 20 mg of finely ground lithium iron phosphate powder is weighed out and set aside. 20 mg of PVP and 4 mL of methanol are added to a centrifuge tube and stirred at room temperature to obtain a uniform mixed solution. 2 mL of NMP is slowly added and stirred. The mixture is stirred at 40°C for 24 h to completely dissolve the NMP.
7. The method for preparing a conductive gel based on lithium iron phosphate waste according to claim 3, characterized in that, In step 3, the weighed lithium iron phosphate waste powder is added to the obtained transparent composite gel and ultrasonicated for 60 minutes at a power of 300W to completely dissolve it, resulting in a black lithium iron phosphate waste conductive gel.
8. The method for preparing a conductive gel based on lithium iron phosphate waste according to claim 3, characterized in that, The methanol can be replaced by water or ethanol.